Coronary artery bifurcation narrowing treated by Axxess stent implantation: The CARINAX registry. Issue 4 (29th July 2016) - Briguori, Carlo; Donahue, Michael; Visconti, Gabriella; Focaccio, Amelia; Pennacchi, Mauro; Lucisano, Luigi; Stio, Rocco; Mancone, Massimo; Calcagno, Simone; Di Palma, Vito; Labalestra, Nicola; Signoriello, Giuseppe; et al.
Abstract : Objectives: To compare the safety and efficacy of the Axxess™ biolimus‐eluting stent with the second‐generation drug‐eluting stent (DES) in the treatment of bifurcation lesions. Background: The Axxess™ is a dedicated bifurcation stent, designed to cover the lesion at the carina level. Methods: Between April 2012 and August 2014, 165 patients with de novo bifurcation lesions were treated with the Axxess™ stent (Axxess group). A propensity‐score matched group of 165 patients treated with DES in the same period was selected (Control group). The primary objectives were (1) the procedural complication rate, including side branch (SB) occlusion and trouble in SB access after main vessel stenting; and (2) the device, the angiographic, and the procedural success rate. Results: Procedural complications occurred in 1 patient (0.6%) in the Axxess group and in 20 patients (12%) in the Control group (OR = 0.03; 95% confidence interval 0.005–0.27; P  < 0.001). Device success was obtained in 164 (99.5%) patients in the Axxess group and in all in the Control group ( P  = 1.00). Angiographic success was obtained in all patients. Inaccurate Axxess™ stent position occurred in 21 (13%) patients, and was more often associated with moderate‐to‐severe calcifications and distal lesion site. Procedural success was obtained in 91.5% patients in the Axxess group and in 90% patients in the Control group ( P  = 0.72). Conclusions: The present registry suggests that the Axxess™ stent (1) may represent a valid alternative approach for the treatment of bifurcation lesions and (2) should be avoided in moderate‐to‐severe calcifications and/or in distal lesions. © 2016 Wiley Periodicals, Inc.